2015
DOI: 10.1037/xhp0000061
|View full text |Cite
|
Sign up to set email alerts
|

Binding biological motion and visual features in working memory.

Abstract: Working memory mechanisms for binding have been examined extensively in the last decade, yet few studies have explored bindings relating to human biological motion (BM). Human BM is the most salient and biologically significant kinetic information encountered in everyday life and is stored independently from other visual features (e.g., colors). The current study explored 3 critical issues of BM-related binding in working memory: (a) how many BM binding units can be retained in working memory, (b) whether invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(85 citation statements)
references
References 114 publications
9
72
3
Order By: Relevance
“…For example, one previous behavioral study found that the dual task for actions and colored dots did not affect behavioral performance (Wood, a). A more recent VSTM study showed that changing the color of biological motion stimuli did not affect the behavioral performance for actions, and changing the motions did not affect the performance for colors either (Ding et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one previous behavioral study found that the dual task for actions and colored dots did not affect behavioral performance (Wood, a). A more recent VSTM study showed that changing the color of biological motion stimuli did not affect the behavioral performance for actions, and changing the motions did not affect the performance for colors either (Ding et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on VSTM have focused on three separate systems: an object/agent recognition system that maintains identity information (what/who is involved in the event), a place recognition system that maintains location information (where the event takes place), and an object tracking system that maintains action information (what happens; Wood, a). Preliminary support for this “core knowledge” architecture of VSTM has come from experiments that found independent storage capacity limits for actions, objects, and locations (Shen, Gao, Ding, Zhou, & Huang, ; Wood, a) and from studies that showed impaired performance of VSTM of actions when they were bound with agents or locations (Ding et al, ; Wood, ). This core knowledge architecture in VSTM is also in line with the sensory‐recruitment theory of VSTM, which posits that the stimulus‐specific sensorimotor cortices (i.e., regions involved in perception) are also engaged in the temporary maintenance of the perceived representations, whereas the fronto–parietal network (FPN) is involved in allocating attention to the maintained representations (D'Esposito & Postle, ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies predominantly focused on the WM storage of the pure action information embedded in BMs. For instance, WM can retain three to four individual actions that are stored independently from location, color, shape, and color-shape binding (e.g., Cai et al, 2018;Gao, Bentin, & Shen, 2015;Lu et al, 2016;Shen, Gao, Ding, Zhou, & Huang, 2014;Wood, 2007Wood, , 2011; storing actionrelated binding is resource-demanding (e.g., Ding et al, 2015;Liu, Lu, Wu, Shen, & Gao, 2019;Lu, Ma, Zhao, Gao, & Shen, 2019). To isolate pure action information, the tested BM stimuli were in fact collected from a single actor in almost all WM studies of BM (e.g., the BMs from the widely used Vanrie & Verfaillie, 2004, database were acquired from one actor).…”
Section: Introductionmentioning
confidence: 99%
“…Or it may be that the object-location binding of BM was relatively difficult, since there was a similar observation Participants were presented with one or five point-light walkers for variable durations (500; 1,000;, 2,500; or 5,000 ms) followed by motion masks for 200 ms. After a blank period of 1 s, a probe item was presented, and participants adjusted the heading direction of the probe walker to match that of the item that had been presented at the same location in the sample array. The circling arrow in the right-most panel is shown for illustrative purposes only and was not actually presented that the color-action binding of BM was severely limited in capacity (Ding et al, 2015).…”
Section: Resultsmentioning
confidence: 99%